The State as Mujahid: Jihadist Norms in International Narrative of Saudi Arabia - Boylen, Terence Connor (Curtin University, 2023)
This study explored Saudi narrative for the expression of jihadist norms and tested the extent to which Critical Constructivism can account for the presence (or absence) of those norms. Rather than identifying jihadist norms, this study found that contra-norms are expressed in Saudi narrative. These are expressed in a complex way, preserving the legitimacy of Saudi Arabia in multiple theatres. Further, it found Critical Constructivism is sufficient to explain the presence of these norms given the various power dynamics.